2011
DOI: 10.1007/s11249-011-9808-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Tribological Behavior of Laser in Situ Synthesized TiC-Reinforced Fe-Based Composite Coatings

Abstract: Fe-based composite coatings reinforced with TiC particles were prepared by laser surface engineering from precursor of ferrotitanium and graphite. Microstructure of the composite coatings was comprised of dendritic TiC dispersed in a ferrite matrix. In situ dendritic TiC was formed by mechanism of precipitating from the liquid Fe-Ti-C alloy system. Composite coatings showed a substantial increase in microhardness in comparison to that of the substrate. Dry sliding wear tests performed at room temperature revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…TiC particles are a widely used reinforcement phase that is employed to produce metal matrix composite [16,17]. It is reported that TiC/Fe composite coating layers have higher wear resistance in dry sliding conditions and can drastically reduce scratching and plastic deformation on the contact surface [18]. Modi et al [19] produced coating layers with Fe-TiC composite and commercial cobalt base (Stellite 6) powders on En31 steel by the tungsten inert gas welding process.…”
Section: Introductionmentioning
confidence: 99%
“…TiC particles are a widely used reinforcement phase that is employed to produce metal matrix composite [16,17]. It is reported that TiC/Fe composite coating layers have higher wear resistance in dry sliding conditions and can drastically reduce scratching and plastic deformation on the contact surface [18]. Modi et al [19] produced coating layers with Fe-TiC composite and commercial cobalt base (Stellite 6) powders on En31 steel by the tungsten inert gas welding process.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this may be explained as follows. First, TiC, acting as a strengthening phase, can effectively reduce the plastic deformation of the matrix during sliding, thus improving the wear resistance of the composites [46]. Second, the grain sizes of the HEA-TiC composites were lower than that of the HEA.…”
Section: Wear Behaviormentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Among those materials, TiC and TiN exhibit an inherent spectral selectivity which can be used for delivering high-performance SSAs. [17][18][19] However, they tend to oxidize in the targeted operating temperature range. [20][21][22] As most single-phase materials do not naturally have the required behavior (in terms of both thermal stability and spectral selectivity) as SSAs, how can we further enhance the working temperature of SSAs beyond 600 1C?…”
Section: Introductionmentioning
confidence: 99%